The Effect of Audiovisual Dissemination on Students 13 – 14 Years Old to Oral Hygiene Status - Dyah Triswari; Rr. Aulia Quinta Zashika (Journal of Indonesian Dental Association, 2019)
Introduction: Dental and oral health problems in children, especially caries, increase at age 10-14 years old due to the lack of children’s knowledge. Knowledge can be provided through dissemination. Dissemination can be delivered by audio-visual media that is easy to be understand and remember. Objective: To determine the influence of dissemination using audio-visual media on 13-14 years old students at Islamic Center Bin Baz Yogyakarta Boarding School (ICBB) of oral hygiene status. Methods: This research used experimental quasy method with one group pre-test and post-test design on 60 subjects at ICBB. Pre-test and post-test assessments include oral hygiene status measurement before and after the dissemination. This studies lasted 35 days with three times dissemination repetition within 14 days interval. Data analysis were used Paired Simple T-Test. Result: The average of oral hygiene status using Simplified Oral Hygiene Index (OHI-S) decreased from 2,58 to 0,96. The result retrieved from Paired Simple T-Test obtained p value 0,000 (p<0,05) showed that there was significant difference of oral hygiene status average before and after the dissemination was delivered. Conclusion: This study showed that audio-visual media dissemination may affect oral hygiene status on students 13-14 years old at Salafiyah Wustha Islamic Center Bin Baz Yogyakarta Islamic Boarding School.